Editorial - Thomas, Joby (Atna Journal of Tourism Studies, 2016)
This issue of Atna, the Journal of Tourism Studies marks the completion of ten successful years of the journal.The journal began its journey in the year 2006 with the objective to create a platform to publish good research based articles in the discipline of tourism,and thus promotelearning and research in tourism.It gives us immense pleasure tothank allof you, our Members of the EditorialBoard, Referees, Authors and Readers for your strong patronage to the journal.